(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: SMEs are increasingly using social media to improve their visibility, communication, and reach in the market. It has become important to understand what drives SME’s social media usage because its adoption influences business performance. Purpose: This study aims to investigate the factors contributing to the adoption of social media by SMEs and the relationship between social media adoption and performance. It focuses on the interaction of four key factors: perceived ease of use (PEU), cost-efficiency (CE), compatibility (COMP), and trust (TR), in relation to the social media usage of SMEs and their outcomes, utilizing DOI theory. Design/methodology/approach: This study employed an explanatory research design, collecting data from 240 SMEs in Kathmandu, Nepal, through a structured questionnaire survey. PLS SEM was employed to test the proposed hypotheses. Findings: The results revealed that elements such as perceived ease of use, cost-effectiveness, compatibility, and trust influence social media use among SMEs. The findings also showed that SMU significantly mediated the relationship between PEOU, COE, COMP, and T on SMEP. Conclusion: This study has implications for recognizing the significance and advantages of social media and providing theoretical and practical guidance to inform and support organizations in the strategic adoption of social media for business purposes. Keywords: Social Media Utilization, SME Performance, PLS SEM